(NuKRA)QÇNA(B. (NnAUKA Æ KULXTURA (B:s)E (N]OR)QÆ^NIK (B/s)E (NwYP(B. 33s - (N{PAK(B, (NaNATOL)QÆJ(B,s)E; (NgURA(B, (NwOLODIMIR(B,s; (NkREMENX(B, (NwASILX(B,s; (NkURAS(B, )Qæ(NWAN(B,s)E ((NkI)QÇW (B:s)E (NzNANNQ(B,s, 2005)
[(NnAUKA )QÆ MISTECTWO(B, (NLÆTERATURA Æ ÆSTORÆQ(B, (NPRIRODA Æ L@DINA (B- (NWSE CE WISWÆTL@ÃTXSQ W ]ORÆ^NIKU (B"(NuKRAÇNA(B. (NnAUKA Æ KULXTURA(B"].s)E
(Nl(B-(NRA(B: (NS(B. 75-79s
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NnAUKAs -- (NuKRA)QÇNAs)E; (NkULXTURAs -- (NuKRA)QÇNAs)E; (NNANOTEHNOLOG)QÆÇs)E; (NF)QÆTOTERAPÆQs)E; (NKL)QÆMATs)E